You’ll Find no Doorbell in Arturo Corcuera’s Hospitable House - Faúndez V, Edson (2018)
The poetry of Arturo Corcuera (1935-2017) is one of the most relevant ones produced in Latin America between the second half of the 20th century and the first decade of the 21st. In this article I propose a critical approach to the book “A bordo del Arca” (2006) from the analysis of the relationship that is established between the individual and things. This analysis, which creates a dialogue with the preceding criticism and uses theoretical conceptions mainly from philosophical thinking, will lead to a reflection on the meanings of death, friendship, and hospitality in the work of the Peruvian poet